ijsr 2019
DOI: 10.36106/ijsr/1902915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nasopalatine canal using cone beam computed tomography - A retrospective study

Abstract: Background: Implantology is a very significant branch of dentistry that deals with the rehabilitation of edentulous patients. Thus, knowledge of anatomical variations of related neurovascular structures such as the nasopalatine canal is essential. Aim:The aim of study was to determine the form, length, and diameter of the nasopalatine canal using CBCT. Materials and Methods: In this retrospective study, images were archived from CBCT unit and visualized using Romexis software. The nasopalatine canals of 50 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Mean anteroposterior dimension was increasing with increase in age group, but difference in different age groups was statistically not significant. The findings were supported by findings of Panda et al [ 2 ] and Thakur et al ,[ 8 ] Gopal and Kapoor,[ 19 ] and Sathvik et al ;[ 20 ] however, the difference in values was statistically nonsignificant gender wise and age wise. On the contrary, statistical significant results were found in the study conducted by Görürgöz C et al [ 1 ]…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Mean anteroposterior dimension was increasing with increase in age group, but difference in different age groups was statistically not significant. The findings were supported by findings of Panda et al [ 2 ] and Thakur et al ,[ 8 ] Gopal and Kapoor,[ 19 ] and Sathvik et al ;[ 20 ] however, the difference in values was statistically nonsignificant gender wise and age wise. On the contrary, statistical significant results were found in the study conducted by Görürgöz C et al [ 1 ]…”
Section: Discussionsupporting
confidence: 85%
“…Gender wise no statistically significant difference was seen in mesiodistal dimension of IF; however, the mean diameter was greater in males. Panda et al ,[ 2 ] Rao et al ,[ 17 ] Khojastepour et al ,[ 18 ] and Gopal and Kapoor[ 19 ] also reported similar significant differences. Age-wise mesiodistal dimension was increasing with increase in age group, and difference was statistically highly significant ( P = 0.007).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Gopal and Kapoor[ 9 ] reported that the mean labial cortical bone at palatal, middle, and nasal levels was 6.22 ± 1.73 mm, 6.9 ± 1.87 mm, and 13.48 ± 41.82 mm, respectively. The mean palatal cortical bone at palatal, middle, and nasal levels was 2.87 ± 0.78 mm, 4.48 ± 1.06 mm, and 6.22 ± 1.67 mm, respectively; these results were consistent with our case report which ranges from 1.91 mm to 6.91 mm.…”
Section: Discussionmentioning
confidence: 99%